2008
DOI: 10.1371/journal.pone.0001986
|View full text |Cite
|
Sign up to set email alerts
|

Does Sex Trade with Violence among Genotypes in Drosophila melanogaster?

Abstract: The evolutionary forces shaping the ability to win competitive interactions, such as aggressive encounters, are still poorly understood. Given a fitness advantage for competitive success, variance in aggressive and sexual display traits should be depleted, but a great deal of variation in these traits is consistently found. While life history tradeoffs have been commonly cited as a mechanism for the maintenance of variation, the variability of competing strategies of conspecifics may mean there is no single op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 32 publications
(64 reference statements)
0
15
0
Order By: Relevance
“…However, male-male interactions such as those involved in aggressive encounters may have greater effects on gene expression than male-female interactions. Males of many Drosophila species, including D. melanogaster, compete for mates and territories, and aggressive behavior is correlated with mating success (Dow and von Schilcher 1975); both factors correlated with genotype (Cabral et al 2008). Social experience with other males reduces aggressive behavior during competition for territories, and experienced males are more likely to regain territories (Hoffmann 1990).…”
Section: Discussionmentioning
confidence: 99%
“…However, male-male interactions such as those involved in aggressive encounters may have greater effects on gene expression than male-female interactions. Males of many Drosophila species, including D. melanogaster, compete for mates and territories, and aggressive behavior is correlated with mating success (Dow and von Schilcher 1975); both factors correlated with genotype (Cabral et al 2008). Social experience with other males reduces aggressive behavior during competition for territories, and experienced males are more likely to regain territories (Hoffmann 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Theoretical modeling has suggested that frequency-dependent selection could be generating genetic variation in aggression (Maynard Smith and Harper 1988). The observation that many behavioral phenotypes vary widely in a population is often attributed to life history trade-offs (Cabral et al 2008;Maney 2008); recent work also suggests that animal ''personalities'' within a population might be adaptive (Wolf et al 2007). Another potential explanation is that the pleiotropic nature of many genes affecting aggressive behavior subjects them to opposing or multidirectional selective pressures, maintaining variation.…”
mentioning
confidence: 99%
“…Aggression is heritable in at least four natural populations of Drosophila (Hoffmann, 1988;Edwards et al, 2006;Cabral et al, 2008). Natural genetic variation in aggressiveness influences group formation, including group size (Saltz and Foley, 2011), through processes that are not yet fully understood (Foley et al, 2015).…”
Section: Social Dynamics Of Aggression In Drosophilamentioning
confidence: 99%
“…Natural genetic variation in aggressiveness influences group formation, including group size (Saltz and Foley, 2011), through processes that are not yet fully understood (Foley et al, 2015). Males from natural genotypes modulate their aggressive behavior in response to local ecology and sex ratio (Cacoyianni and Hoffmann, 1990), and natural genotypes show indirect genetic effects, whereby the aggressiveness of a male depends on the genotype of his opponent (Cabral et al, 2008;Saltz, 2013). Complementary work on laboratory genotypes has shown that prior exposure to males (Yurkovic et al, 2006;Wang et al, 2008) and females (Yuan et al, 2014;Baxter et al, 2015) can influence males' later aggression.…”
Section: Social Dynamics Of Aggression In Drosophilamentioning
confidence: 99%
See 1 more Smart Citation